Central meteorológica microcontrolada de baixo custo - Dalla Costa, Mauricio (2014)
This work presents the development of a meteorological station for temperature, atmospheric pressure, relative humidity, wind speed and direction monitoring. Sensors provide meteorological data in a given time interval for a microcontrolled system that processes such data and sends them to a computer through a serial communication interface based on RS-232 protocol, allowing the user to visualize and store the information in a communication terminal software. The results are presented and discussed at the end of this work, showing a screen reading program in computer graphics and with the meteorological data measured at the station.